Combining X-ray micro-CT and microscopy-based images of two lianas species to derive structural, mechanical and functional relationships - Claudine Karlen; Pascal Turberg; Alexandre Buttler; Océane Martin; Fritz Schweingruber; Anastasios P. Vassilopoulos (Plant Systematics and Evolution, 2024)
This paper presents a biomechanical study of stems of two liana species, Clematis vitalba and Vitis vinifera , investigates the mechanical performance of these two liana species and attempts to enhance the understanding of structure–function relationships. The investigation involved mechanical testing of whole plant stems, supplemented by X-ray micro-CT (X-ray computed tomography at micron voxel size) imaging and 2D microscopic images of stained cross sections of the plant stems, to derive structure–function relationships with potential for application in bioinspired composite materials. The micro-CT images were compared to the microscopic images of stained cross sections, in order to show benefits and potential drawbacks of the X-ray micro-CT method with respect to traditional methods. The high-resolution 3D imaging capacity of micro-CT is exploited to explain the structural functionality derived from the mechanical testing. A simple finite element model is developed based on the plant topology derived by the micro-CT images and proved accurate enough to model the plant’s mechanical behaviour and assess the influence of their structural differences. The two plants exhibit different to each other physical and mechanical properties (density, strength and stiffness) due to their common growth form. Anatomical cross-sectional observation and X-ray micro-CT provide complementary information. The first method allows the identification of the lignified parts, supposedly more resistant mechanically, of these structures, while the second one provides a full 3D model of the structure, admittedly less detailed but providing the spatial distribution of density contrasts supposed to be important in the mechanical properties of the plant. The proposed methodological approach opens new perspectives to better understand the mechanical behaviour of the complex structure of plants and to draw inspiration from it in structural engineering.

Spatio-temporal patterns and drivers of CH4 and CO2 fluxes from rivers and lakes in highly urbanized areas - Longfeng Fan; Junxiang Cheng; Yangcun Xie; Ligang Xu; Alexandre Buttler; Yuexia Wu; Hongxiang Fan; Yakun Wu (Science of The Total Environment, 2024)

Impacts of snow-farming on alpine soil and vegetation: A case study from the Swiss Alps - Alexandre Buttler; Roland Teuscher; Nicolas Deschamps; Konstantin Gavazov; Luca Bragazza; Pierre Mariotte; Rodolphe Schlaepfer; Vincent E.J. Jassey; Lucas Freund; Jessica Cuartero; Juan Carlos Quezada; Beat Frey (Science of The Total Environment, 2023)

Ericoid shrub encroachment shifts aboveground–belowground linkages in three peatlands across Europe and Western Siberia - Alexandre Buttler; Luca Bragazza; Fatima Laggoun‐Défarge; Sebastien Gogo; Marie‐Laure Toussaint; Mariusz Lamentowicz; Bogdan H. Chojnicki; Michał Słowiński; Sandra Słowińska; Małgorzata Zielińska; Monika Reczuga; Jan Barabach; et al. (Global Change Biology, 2023)
In northern peatlands, reduction of Sphagnum dominance in favour of vascular vegetation is likely to influence biogeochemical processes. Such vegetation changes occur as the water table lowers and temperatures rise. To test which of these factors has a significant influence on peatland vegetation, we conducted a 3‐year manipulative field experiment in Linje mire (northern Poland). We manipulated the peatland water table level (wet, intermediate and dry; on average the depth of the water table was 17.4, 21.2 and 25.3 cm respectively), and we used open‐top chambers (OTCs) to create warmer conditions (on average increase of 1.2°C in OTC plots compared to control plots). Peat drying through water table lowering at this local scale had a larger effect than OTC warming treatment per see on Sphagnum mosses and vascular plants. In particular, ericoid shrubs increased with a lower water table level, while Sphagnum decreased. Microclimatic measurements at the plot scale indicated that both water‐level and temperature, represented by heating degree days (HDDs), can have significant effects on the vegetation. In a large‐scale complementary vegetation gradient survey replicated in three peatlands positioned along a transitional oceanic–continental and temperate–boreal (subarctic) gradient (France–Poland–Western Siberia), an increase in ericoid shrubs was marked by an increase in phenols in peat pore water, resulting from higher phenol concentrations in vascular plant biomass. Our results suggest a shift in functioning from a mineral‐N‐driven to a fungi‐mediated organic‐N nutrient acquisition with shrub encroachment. Both ericoid shrub encroachment and higher mean annual temperature in the three sites triggered greater vascular plant biomass and consequently the dominance of decomposers (especially fungi), which led to a feeding community dominated by nematodes. This contributed to lower enzymatic multifunctionality. Our findings illustrate mechanisms by which plants influence ecosystem responses to climate change, through their effect on microbial trophic interactions.

Food web structure and energy flux dynamics, but not taxonomic richness, influence microbial ecosystem functions in a Sphagnum-dominated peatland - Vincent E.J. Jassey; Owen L. Petchey; Philippe Binet; Alexandre Buttler; Geneviève Chiapusio; Frédéric Delarue; Fatima Laggoun-Défarge; Daniel Gilbert; Edward A.D. Mitchell; Janna M. Barel (European Journal of Soil Biology, 2023)

Deforestation‐free land‐use change and organic matter‐centered management improve the C footprint of oil palm expansion - Juan Carlos Quezada; Thomas Guillaume; Christopher Poeplau; Jaboury Ghazoul; Alexandre Buttler (Global Change Biology, 2022)
In recent decades, mounting evidence has indicated that the expansion of oil palm (OP) plantations at the expense of tropical forest has had a far pernicious effect on ecosystem aspects. While various deforestation‐free strategies have been proposed to enhance OP sustainability, field‐based evidence still need to be consolidated, in particular with respect to savanna regions where OP expansion has recently occurred and that present large area with potential for OP cultivation. Here we show that the common management practice creating within the plantation the so‐called management zones explained nearly five times more variability of soil biogeochemical properties than the savanna land‐use change per se. We also found that clayey‐soil savanna conversion into OP increased total ecosystem C stocks by 40 ± 13 Mg C ha −1 during a full OP cultivation cycle, which was due to the higher OP‐derived C accumulated in the biomass and in the soil as compared to the loss of savanna‐derived C. In addition, application of organic residues in specific management zones enhanced the accumulation of soil organic carbon by up to 1.9 Mg ha −1 year −1 over the full cycle. Within plantation, zones subjected to organic amendments sustained similar soil microbial activity as in neighboring savannas. Our findings represent an empirical proof‐of‐concept that the conversion of non‐forested land in parallel with organic matter‐oriented management strategies can enhance OP agroecosystems C sink capacity while promoting microbe‐mediated soil functioning. Nonetheless, savannas are unique and threatened ecosystems that support a vast biodiversity. Therefore, we suggest to give priority attention to conservation of natural savannas and direct more research toward the impacts of the conversion and subsequent management of degraded savannas.

Species identity, rather than species mixtures, drives cover crop effects on nutrient partitioning in unfertilized agricultural soil - Lucas Freund; Pierre Mariotte; Mathieu Santonja; Alexandre Buttler; Bernard Jeangros (Plant and Soil, 2021)
Aims Previous cover crop studies mainly focused on the links between plant uptake and soil fertility, and there is a clear knowledge gap regarding the role of microbes in these processes. Our aim was then to better understand the effects of plant mixtures (versus monoculture) and the specific effects of each plant species on nitrogen (N) and phosphorus (P) partitioning between plant, soil, and more particularly microbial pools. Methods Monocultures and mixtures composed of black oat, field pea and Indian mustard were grown during two months in a greenhouse. The concentrations of carbon (C), N and P were measured in both plant and microbial biomass at final harvest, together with soil available N and P. Results Overall, our findings highlight stronger selection effect (i.e. , presence of key species) rather than complementarity effects (i.e. , species mixture) to affect the measured parameters. The presence of pea increased the biomass production of oat and mustard, as well as the nutrient concentration of oat, whereas pea P concentration decreased in presence of oat and mustard N and P concentrations were negatively impacted respectively by the presence of oat and pea. We also observed a strong competition between plants and microbes for both soil N and P. Conclusions The oat-pea and the oat-pea-mustard mixtures represented the best compromise between biomass production, nutrient storage and biomass C:N ratio, thus insuring a good organic matter decomposition and nutrient provision for the following main crop.

Do wind turbines impact plant community properties in mountain region? - Ileana Pătru-Stupariu; Ana-Maria Calotă; Mathieu Santonja; Paulina Anastasiu; Ioana Stoicescu; Iovu Adrian Biriş; Mihai-Sorin Stupariu; Alexandre Buttler (Biologia, 2019)

Linking soil's volatilome to microbes and plant roots highlights the importance of microbes as emitters of belowground volatile signals - Denis Schenkel; Aurélie Deveau; Jun Niimi; Pierre Mariotte; Amarante Vitra; Marco Meisser; Alexandre Buttler; Richard Splivallo (Environmental Microbiology, 2019)
Summary Plants and microbes release a plethora of volatiles that act as signals in plant–microbe interactions. Characterizing soil's volatilome and microbiome might shed light on the nature of relevant volatile signals and on their emitters. This hypothesis was tested by characterizing plant cover, soil's volatilome, nutrient content and microbiomes in three grasslands of the Swiss Jura Mountains. The fingerprints of soil's volatiles were generated by solid‐phase micro‐extraction gas chromatography/mass spectrometry, whereas high‐throughput sequencing was used to create a snapshot of soil's microbial communities. A high similarity was observed in plant communities of two out of three sites, which was mirrored by the soil's volatilome. Multiple factor analysis evidenced a strong association among soil's volatilome, plant and microbial communities. The proportion of volatiles correlated to single bacterial and fungal taxa was higher than for plants. This suggests that those organisms might be major contributors to the volatilome of grassland soils. These findings illustrate that key volatiles in grassland soils might be emitted by a handful of organisms that include specific plants and microbes. Further work will be needed to unravel the structure of belowground volatiles and understand their implications for plant health and development.

Sphagnum Species Modulate their Phenolic Profiles and Mycorrhizal Colonization of Surrounding Andromeda polifolia along Peatland Microhabitats - Geneviève Chiapusio; Vincent E. J. Jassey; Floriant Bellvert; Gilles Comte; Leslie A. Weston; Frederic Delarue; Alexandre Buttler; Marie Laure Toussaint; Philippe Binet (Journal of Chemical Ecology, 2018)

Vascular plant‐mediated controls on atmospheric carbon assimilation and peat carbon decomposition under climate change - Konstantin Gavazov; Remy Albrecht; Alexandre Buttler; Ellen Dorrepaal; Mark H. Garnett; Sebastien Gogo; Frank Hagedorn; Robert T. E. Mills; Bjorn J. M. Robroek; Luca Bragazza (Global Change Biology, 2018)
Climate change can alter peatland plant community composition by promoting the growth of vascular plants. How such vegetation change affects peatland carbon dynamics remains, however, unclear. In order to assess the effect of vegetation change on carbon uptake and release, we performed a vascular plant‐removal experiment in two Sphagnum ‐dominated peatlands that represent contrasting stages of natural vegetation succession along a climatic gradient. Periodic measurements of net ecosystem CO 2 exchange revealed that vascular plants play a crucial role in assuring the potential for net carbon uptake, particularly with a warmer climate. The presence of vascular plants, however, also increased ecosystem respiration, and by using the seasonal variation of respired CO 2 radiocarbon (bomb‐ 14 C) signature we demonstrate an enhanced heterotrophic decomposition of peat carbon due to rhizosphere priming. The observed rhizosphere priming of peat carbon decomposition was matched by more advanced humification of dissolved organic matter, which remained apparent beyond the plant growing season. Our results underline the relevance of rhizosphere priming in peatlands, especially when assessing the future carbon sink function of peatlands undergoing a shift in vegetation community composition in association with climate change.

The Impact of Experimental Temperature and Water Level Manipulation on Carbon Dioxide Release in a Poor Fen in Northern Poland - Mateusz Samson; Sandra Słowińska; Michał Słowiński; Mariusz Lamentowicz; Jan Barabach; Kamila Harenda; Małgorzata Zielińska; Bjorn J. M. Robroek; Vincent E. J. Jassey; Alexandre Buttler; Bogdan H. Chojnicki (Wetlands, 2018)

Litter decomposition in peatlands is promoted by mixed plants - Fabien Leroy; Sébastien Gogo; Alexandre Buttler; Luca Bragazza; Fatima Laggoun-Défarge (Journal of Soils and Sediments, 2018)

Vapor–pressure deficit and extreme climatic variables limit tree growth - Paula Sanginés de Cárcer; Yann Vitasse; Josep Peñuelas; Vincent E. J. Jassey; Alexandre Buttler; Constant Signarbieux (Global Change Biology, 2018)
Assessing the effect of global warming on forest growth requires a better understanding of species‐specific responses to climate change conditions. Norway spruce and European beech are among the dominant tree species in Europe and are largely used by the timber industry. Their sensitivity to changes in climate and extreme climatic events, however, endangers their future sustainability. Identifying the key climatic factors limiting their growth and survival is therefore crucial for assessing the responses of these two species to ongoing climate change. We studied the vulnerability of beech and spruce to warmer and drier conditions by transplanting saplings from the top to the bottom of an elevational gradient in the Jura Mountains in Switzerland. We (1) demonstrated that a longer growing season due to warming could not fully account for the positive growth responses, and the positive effect on sapling productivity was species‐dependent, (2) demonstrated that the contrasting growth responses of beech and spruce were mainly due to different sensitivities to elevated vapor–pressure deficits ( VPD ), (3) determined the species‐specific limits to VPD above which growth rate began to decline, and (4) demonstrated that models incorporating extreme climatic events could account for the response of growth to warming better than models using only average values. These results support that the sustainability of forest trees in the coming decades will depend on how extreme climatic events will change, irrespective of the overall warming trend.

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Asymmetric effects of cooler and warmer winters on beech phenology last beyond spring - Constant Signarbieux; Ester Toledano; Paula Sanginés de Carcer; Yongshuo H. Fu; Rodolphe Schlaepfer; Alexandre Buttler; Yann Vitasse (Global Change Biology, 2017)
In temperate trees, the timings of plant growth onset and cessation affect biogeochemical cycles, water, and energy balance. Currently, phenological studies largely focus on specific phenophases and on their responses to warming. How differently spring phenology responds to the warming and cooling, and affects the subsequent phases, has not been yet investigated in trees. Here, we exposed saplings of Fagus sylvatica L. to warmer and cooler climate during the winter 2013–2014 by conducting a reciprocal transplant experiment between two elevations (1,340 vs. 371 m a.s.l., ca. 6°C difference) in the Swiss Jura mountains. To test the legacy effects of earlier or later budburst on the budset timing, saplings were moved back to their original elevation shortly after the occurrence of budburst in spring 2014. One degree decrease in air temperature in winter/spring resulted in a delay of 10.9 days in budburst dates, whereas one degree of warming advanced the date by 8.8 days. Interestingly, we also found an asymmetric effect of the warmer winter vs. cooler winter on the budset timing in late summer. Budset of saplings that experienced a cooler winter was delayed by 31 days compared to the control, whereas it was delayed by only 10 days in saplings that experienced a warmer winter. Budburst timing in 2015 was not significantly impacted by the artificial advance or delay of the budburst timing in 2014, indicating that the legacy effects of the different phenophases might be reset during each winter. Adapting phenological models to the whole annual phenological cycle, and considering the different response to cooling and warming, would improve predictions of tree phenology under future climate warming conditions.

Response to Editor to the comment by Delarue (2016) to our paper entitled ‘Persistent high temperature and low precipitation reduce peat carbon accumulation’ - Luca Bragazza; Alexandre Buttler; Bjorn J. M. Robroek; Remy Albrecht; Claudio Zaccone; Vincent E. J. Jassey; Constant Signarbieux (Global Change Biology, 2017)

Persistent high temperature and low precipitation reduce peat carbon accumulation - Luca Bragazza; Alexandre Buttler; Bjorn J.M. Robroek; Remy Albrecht; Claudio Zaccone; Vincent E.J. Jassey; Constant Signarbieux (Global Change Biology, 2016)
Extreme climate events are predicted to become more frequent and intense. Their ecological impacts, particularly on carbon cycling, can differ in relation to ecosystem sensitivity. Peatlands, being characterized by peat accumulation under waterlogged conditions, can be particularly sensitive to climate extremes if the climate event increases soil oxygenation. However, a mechanistic understanding of peatland responses to persistent climate extremes is still lacking, particularly in terms of aboveground–belowground feedback. Here, we present the results of a transplantation experiment of peat mesocosms from high to low altitude in order to simulate, during 3 years, a mean annual temperature c. 5 °C higher and a mean annual precipitation c. 60% lower. Specifically, we aim at understanding the intensity of changes for a set of biogeochemical processes and their feedback on carbon accumulation. In the transplanted mesocosms, plant productivity showed a species‐specific response depending on plant growth forms, with a significant decrease (c. 60%) in peat moss productivity. Soil respiration almost doubled and Q 10 halved in the transplanted mesocosms in combination with an increase in activity of soil enzymes. Spectroscopic characterization of peat chemistry in the transplanted mesocosms confirmed the deepening of soil oxygenation which, in turn, stimulated microbial decomposition. After 3 years, soil carbon stock increased only in the control mesocosms whereas a reduction in mean annual carbon accumulation of c. 30% was observed in the transplanted mesocosms. Based on the above information, a structural equation model was built to provide a mechanistic understanding of the causal connections between peat moisture, vegetation response, soil respiration and carbon accumulation. This study identifies, in the feedback between plant and microbial responses, the primary pathways explaining the reduction in carbon accumulation in response to recurring climate extremes in peat soils.

Peatland vascular plant functional types affect dissolved organic matter chemistry - Bjorn J. M. Robroek; Remy J. H. Albrecht; Samuel Hamard; Adrian Pulgarin; Luca Bragazza; Alexandre Buttler; Vincent EJ Jassey (Plant and Soil, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Environmental drivers of carbon and nitrogen isotopic signatures in peatland vascular plants along an altitude gradient - Konstantin Gavazov; Frank Hagedorn; Alexandre Buttler; Rolf Siegwolf; Luca Bragazza (Oecologia, 2016)

Biotic and Abiotic Constraints on the Decomposition of Fagus sylvatica Leaf Litter Along an Altitudinal Gradient in Contrasting Land-Use Types - Konstantin Gavazov; Robert Mills; Thomas Spiegelberger; Jonathan Lenglet; Alexandre Buttler (Ecosystems, 2014)

Indirect effects of experimental warming on dissolved organic carbon content in subsurface peat - Frédéric Delarue; Sébastien Gogo; Alexandre Buttler; Luca Bragazza; Vincent E. J. Jassey; Grégory Bernard; Fatima Laggoun-Défarge (Journal of Soils and Sediments, 2014)

Transplantation of subalpine wood-pasture turfs along a natural climatic gradient reveals lower resistance of unwooded pastures to climate change compared to wooded ones - Konstantin Gavazov; Thomas Spiegelberger; Alexandre Buttler (Oecologia, 2014)

Snow cover manipulation effects on microbial community structure and soil chemistry in a mountain bog - Bjorn J. M. Robroek; Amber Heijboer; Vincent E. J. Jassey; Mariet M. Hefting; T. Gerrit Rouwenhorst; Alexandre Buttler; Luca Bragazza (Plant and Soil, 2013)

Arbuscular mycorrhizal fungi reduce the differences in competitiveness between dominant and subordinate plant species - Pierre Mariotte; Claire Meugnier; David Johnson; Aurélie Thébault; Thomas Spiegelberger; Alexandre Buttler (Mycorrhiza, 2013)

Above‐ and belowground linkages in Sphagnum peatland: climate warming affects plant‐microbial interactions - Vincent EJ Jassey; Geneviève Chiapusio; Philippe Binet; Alexandre Buttler; Fatima Laggoun‐Défarge; Frédéric Delarue; Nadine Bernard; Edward AD Mitchell; Marie‐Laure Toussaint; André‐Jean Francez; Daniel Gilbert (Global Change Biology, 2013)
Peatlands contain approximately one third of all soil organic carbon ( SOC ). Warming can alter above‐ and belowground linkages that regulate soil organic carbon dynamics and C ‐balance in peatlands. Here we examine the multiyear impact of in situ experimental warming on the microbial food web, vegetation, and their feedbacks with soil chemistry. We provide evidence of both positive and negative impacts of warming on specific microbial functional groups, leading to destabilization of the microbial food web. We observed a strong reduction (70%) in the biomass of top‐predators (testate amoebae) in warmed plots. Such a loss caused a shortening of microbial food chains, which in turn stimulated microbial activity, leading to slight increases in levels of nutrients and labile C in water. We further show that warming altered the regulatory role of Sphagnum ‐polyphenols on microbial community structure with a potential inhibition of top predators. In addition, warming caused a decrease in Sphagnum cover and an increase in vascular plant cover. Using structural equation modelling, we show that changes in the microbial food web affected the relationships between plants, soil water chemistry, and microbial communities. These results suggest that warming will destabilize C and nutrient recycling of peatlands via changes in above‐ and belowground linkages, and therefore, the microbial food web associated with mosses will feedback positively to global warming by destabilizing the carbon cycle. This study confirms that microbial food webs thus constitute a key element in the functioning of peatland ecosystems. Their study can help understand how mosses, as ecosystem engineers, tightly regulate biogeochemical cycling and climate feedback in peatlands

Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Andy Siegenthaler; Alexandre Buttler; Philippe Grosvernier; Jean-Michel Gobat; Mats B. Nilsson; Edward A. D. Mitchell (Oecologia, 2013)

Complex interactions between spatial pattern of resident species and invasiveness of newly arriving species affect invasibility - Aurélie Thébault; Peter Stoll; Alexandre Buttler (Oecologia, 2012)

The relationship between plant species richness and soil aggregate stability can depend on disturbance - Mandy Pohl; Frank Graf; Alexandre Buttler; Christian Rixen (Plant and Soil, 2012)

High nitrogen deposition alters the decomposition of bog plant litter and reduces carbon accumulation - Luca Bragazza; Alexandre Buttler; Jonathan Habermacher; Lisa Brancaleoni; Renato Gerdol; Hannu Fritze; Peter Hanajík; Raija Laiho; David Johnson (Global Change Biology, 2012)
Bogs are globally important sinks of atmospheric carbon ( C ) due to the accumulation of partially decomposed litter that forms peat. Because bogs receive their nutrients from the atmosphere, the world‐wide increase of nitrogen ( N ) deposition is expected to affect litter decomposition and, ultimately, the rate of C accumulation. However, the mechanism of such biogeochemical alteration remains unclear and quantification of the effect of N addition on litter accumulation has yet to be done. Here, we show that 7 years of N addition to a bog decreased the C : N ratio, increased the bacterial biomass and stimulated the activity of hydrolytic and oxidative enzymes in surface peat. Furthermore, N addition modified nutrient limitation of microbes during litter decomposition so that phosphorus became a primary limiting nutrient. Alteration of N release from decomposing litter affected bog water chemistry and the competitive balance between peat‐forming mosses and vascular plants. We estimate that deposition of about 4 g N m −2 yr −1 will cause a mean annual reduction of fresh litter C accumulation of about 40 g m −2 primarily as a consequence of decreased litter production from peat‐forming mosses. Our findings show that N deposition interacts with both above and below ground components of biodiversity to threaten the ability of bogs to act as N ‐sinks, which may offset the positive effects of N on C accumulation seen in other ecosystems.

Patterns of bryophyte and vascular plant richness in European subalpine springs - Lucia Sekulová; Michal Hájek; Petra Hájková; Eva Mikulášková; Alexandre Buttler; Vít Syrovátka; Zuzana Rozbrojová (Plant Ecology, 2012)

Experimental climate effect on seasonal variability of polyphenol/phenoloxidase interplay along a narrow fen–bog ecological gradient in Sphagnum fallax - VINCENT E. J. JASSEY; GENEVIÈVE CHIAPUSIO; DANIEL GILBERT; ALEXANDRE BUTTLER; MARIE‐LAURE TOUSSAINT; PHILIPPE BINET (Global Change Biology, 2011)
Extracellular phenoloxidase enzymes play an important role in the stability of soil carbon storage by contributing to the cycling of complex recalcitrant phenolic compounds. Climate warming could affect peatland functioning through an alteration of polyphenol/phenoloxidase interplay, which could lead them to becoming weaker sinks of carbon. Here, we assessed the seasonal variability of total phenolics and phenoloxidases subjected to 2–3 °C increase in air temperature using open‐top chambers. The measurements were performed along a narrow fen–bog ecological gradient over one growing season. Climate warming had a weak effect on phenoloxidases, but reduced phenolics in both fen and bog areas. Multivariate analyses revealed a split between the areas and also showed that climate warming exacerbated the seasonal variability of polyphenols, culminating in a destabilization of the carbon cycle. A negative relationship between polyphenols and phenoloxidases was recorded in controls and climate treatments suggesting an inhibitory effect of phenolics on phenoloxidases. Any significant decrease of phenolics through repeatedly elevated temperature would greatly impact the ecosystem functioning and carbon cycle through an alteration of the interaction of polyphenols with microbial communities and the production of extracellular enzymes. Our climate treatments did not have the same impact along the fen–bog gradient and suggested that not all the peatland habitats would respond similarly to climate forcing.

Polyploidy and invasion success: trait trade-offs in native and introduced cytotypes of two Asteraceae species - Aurélie Thébault; François Gillet; Heinz Müller-Schärer; Alexandre Buttler (Plant Ecology, 2011)

Species-specific effects of polyploidisation and plant traits of Centaurea maculosa and Senecio inaequidens on rhizosphere microorganisms - Aurélie Thébault; Beat Frey; Edward A. D. Mitchell; Alexandre Buttler (Oecologia, 2010)

Pollen productivity estimates and relevant source area of pollen for selected plant taxa in a pasture woodland landscape of the Jura Mountains (Switzerland) - Florence Mazier; Anna Broström; Marie-José Gaillard; Shinya Sugita; Pascal Vittoz; Alexandre Buttler (Vegetation History and Archaeobotany, 2008)

Short-Term Effects of Cattle Browsing on Tree Sapling Growth in Mountain Wooded Pastures - Charlotte Vandenberghe; François Freléchoux; Marie-Agnès Moravie; Fawziah Gadallah; Alexandre Buttler (Plant Ecology, 2007)

Modern pollen/vegetation/land-use relationships in mountain environments: an example from the Champsaur valley (French Alps) - Mona Court-Picon; Alexandre Buttler; Jacques-Louis de Beaulieu (Vegetation History and Archaeobotany, 2006)

Potassium limits potential growth of bog vegetation under elevated atmospheric CO 2 and N deposition - MARCEL R. HOOSBEEK; NICO VAN BREEMEN; HARRI VASANDER; ALEXANDRE BUTTLER; FRANK BERENDSE (Global Change Biology, 2002)
The free air carbon dioxide enrichment (FACE) and N deposition experiments on four ombrotrophic bogs in Finland, Sweden, the Netherlands and Switzerland, revealed that after three years of treatment: (1) elevated atmospheric CO 2 concentration had no significant effect on the biomass growth of Sphagnum and vascular species; and (2) increased N deposition reduced Sphagnum growth, because it increased the cover of vascular plants and the tall moss Polytrichum strictum , while vascular plant biomass growth was not affected. This paper focuses on water chemistry, plant nutrient content, and litter decomposition rates. Potassium limitation, or low supply of K and P, may have prevented a significant increase of Sphagnum growth under elevated CO 2 and N deposition. Vascular plant growth under elevated CO 2 and N deposition was also limited by K, or by K in combination with P or N (N in CO 2 experiment). Elevated CO 2 and N deposition had no effect on decomposition rates of Sphagnum and vascular plant litter. Aside from a possible effect of N deposition on light competition between species, we expect that elevated atmospheric CO 2 and N deposition concentrations will not affect Sphagnum and vascular plant growth in bogs of north‐west Europe due to K‐, or K in combination with N‐ or P‐, limited growth. For the same reason we expect no effect of elevated CO 2 and N deposition on litter decomposition. Net primary production of raised ombrotrophic bogs that are at or close to steady state, is regulated by input of nutrients through atmospheric deposition. Therefore, we hypothesize that the expected increase of plant growth under elevated CO 2 and N deposition is diminished by current levels of K (and to some extent P and N) in atmospheric deposition.

Raised atmospheric CO 2 levels and increased N deposition cause shifts in plant species composition and production in Sphagnum bogs - Frank Berendse; Nico Van Breemen; HÅkan Rydin; Alexandre Buttler; Monique Heijmans; Marcel R. Hoosbeek; John A. Lee; Edward Mitchell; Timo Saarinen; Harri Vasander; Bo Wallén (Global Change Biology, 2001)
Part of the missing sink in the global CO 2 budget has been attributed to the positive effects of CO 2 fertilization and N deposition on carbon sequestration in Northern Hemisphere terrestrial ecosystems. The genus Sphagnum is one of the most important groups of plant species sequestrating carbon in temperate and northern bog ecosystems, because of the low decomposability of the dead material it produces. The effects of raised CO 2 and increased atmospheric N deposition on growth of Sphagnum and other plants were studied in bogs at four sites across Western Europe. Contrary to expectations, elevated CO 2 did not significantly affect Sphagnum biomass growth. Increased N deposition reduced Sphagnum mass growth, because it increased the cover of vascular plants and the tall moss Polytrichum strictum . Such changes in plant species composition may decrease carbon sequestration in Sphagnum ‐dominated bog ecosystems.

Dynamics of common reed (Phragmites australisTrin.) in Swiss fens with different management - Sabine Güsewell; Christophe Le Nédic; Alexandre Buttler (Wetlands Ecology and Management, 2000)